THE LATE MEDIEVAL CITY OF THE CHU VALLEY (XIII-XVI CC.) (Journal of history-rus, 2021)
This article examines the role of the Aspara settlement. The article provides archaeological data on the topographic features, found elements of material culture, the possibility of reconstruction of cultural, social life, based on historical, archaeological, ethnographic data about the medieval city. Archaeologi cal research in recent years has largely clarified the state of sedentary culture in the ShuTalas valley. The circle of monuments of the late Middle Ages expanded, collections of material culture were replenished. In the cities of the late Middle Ages, the cultural layers are not very pronounced; they are of certain inter est as an indicator of the general state of the sedentary culture of that period. In addition, the archaeo logical materials of the 13th16th centuries, despite their paucity, deserve attention, since the presence of a local agricultural population in medieval sources and folk was noted in the absence of cities. Aspara is a city surrounded by long walls with dimensions strikingly different from other settlements that existed at that time. Long walls were a kind of indicator of economic and political influence. According to this and other criteria described in this article, Aspara is a unique archaeological site of medieval urban culture on the territory of Kazakhstan.Key words: late Medieval age, culture, archaeology, the Shu Valley, Aspara, Andas Batyr.